Surányi György as "the" manager of the Hungarian monetary policy between 1989 and 2001 - Kerényi Ádám (New Ideas in a Changing World of Business Managament and Marketing, 2015)
Decision makers, analysts and economists seek to learn from the best experts of monetary policy and central banking, in order that they can do better next time, or in order to avoid financial crisis One man’s decisions are always a matter of controversy, only time can decide whether he was right or wrong. In my study I focus on the carrier of Surányi György, who is a professor of Economics in Corvinus Budapest University, he used to be the governor of the Hungarian National Bank. According to several experts Surányi György had a successful experience in policymaking during 1990-1991 and 1995-2001. Surányi was elected to the best central banker of the CEE region several times. In my case study I try to show one debate with George Soros and a management challenge from his carrier. The famous austerity and adjustment program started a stabilization in 1995 was an extremely painful process, which was followed by a heterodox economic policy. This was not based exclusively on budgetary corrections, and even if such corrections were made, they were implemented in a kind of structure that exercised a positive influence on the business sector, the economy and on investments. This is why he succeeded in saving jobs. But the real wages fell by 11 percent in the first year, which put extraordinary burdens on many people, but this was still more tolerable than seeing tens of thousands of workers lose their jobs and join the ranks of the unemployed. This program was not supported by the International Monetary Fund, but was supported by the international financial markets and the business community. After only one year the introduction of the stabilization program the Monetary Fund admitted that the program was working – and fully in line with the previous hopes of the Governor’s.